2000
DOI: 10.1063/1.481227
|View full text |Cite
|
Sign up to set email alerts
|

High pressure Raman scattering studies on adamantane

Abstract: High pressure behavior of adamantane is investigated up to pressures of 26 GPa at ambient temperature using Raman spectroscopy. A detailed study of changes in the Raman spectrum of the C–H stretching modes across the disorder–order transition around 0.5 GPa is reported. Pressure dependence of the internal mode frequencies suggest two more subtle transitions around 2.8 GPa and 8.5 GPa, respectively, which are reversible. Evolution of spectra at higher pressures show evidence for another structural transition ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 30 publications
6
18
0
Order By: Relevance
“…No evidence was found for the formation of higher diamondoids in the current pressure range. The phase transition observed from XRD is related to the intermolecular packing rearrangement and molecular distortion of the [121] tetramantane, as reported in adamantane. , …”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…No evidence was found for the formation of higher diamondoids in the current pressure range. The phase transition observed from XRD is related to the intermolecular packing rearrangement and molecular distortion of the [121] tetramantane, as reported in adamantane. , …”
Section: Discussionmentioning
confidence: 62%
“…In addition, application of pressure to molecular crystals themselves has been of considerable interest for better understanding the interatomic interactions at various length scales. The behavior of diamondoids at high pressure remains largely unexplored in part due to the difficulties in attaining the starting materials, especially higher diamondoids. Only adamantane has been investigated, where a pressure-induced disorder–order transition was observed. , …”
Section: Introductionmentioning
confidence: 99%
“…It is found that the intensity of the C-H stretching peak of ( Fig. 4) In addition, some extra-bands at 1319 cm -1 (twisting vibration of O-H) [25], 1297 cm -1 (C-O-C stretching) [26,27], 1275 cm -1 and 1135 cm -1 (C-O stretching of ester groups) [28][29][30][31][32], and 1225 cm -1 (H-C-C bending and CH 2 twisting) [33,34] appear (Fig. 4).…”
Section: Atr-ftir Analysismentioning
confidence: 99%
“…The diamond-like properties emerge only at the intramolecular sp 3 carbon framework, while their intermolecular interactions and associated properties are not well explored. Pressure, which can dramatically alter a material’s physical and chemical behavior, can provide insight into structure–property relationships and offer an opportunity for optimizing desirable properties. , Pressure-induced bond breaking and bond formation have been documented in many carbon-based molecular systems. So far, however, pressure-driven structural changes in diamondoids are not well understood. …”
mentioning
confidence: 99%
“…All structural transitions are reversible upon releasing pressure. Because of the uncertainties in structural determinations at high pressure, we focused on the structural evolution for the low-pressure phases of all diamondoid crystals studied here, except adamantane which transforms from an orientationally disordered cubic phase to an ordered tetragonal phase at 0.5 GPa. The relative volume changes as a function of pressure for the low-pressure phases of these diamondoid crystals are plotted in Figure a and were fit to a third-order Birch–Murnaghan equation of state (EoS). , (See the Supporting Information for the description of the EoS and the detailed fitting curves of each diamondoid crystal.) Fitting statistics are summarized in Table .…”
mentioning
confidence: 99%